Penelitian Situs Muara Kaman Dan Upaya Pengembangannya - Gunadi Kasnowihardjo (Berkala Arkeologi, 2006)
The Muara Kaman area has been a fairly busy area since the proto-history era because it became a transit area and at the same time a meeting place between people from the interior and traders from outside Kalimantan. How the condition of the Muara Kaman area at that time cannot be explained with complete data, especially how large the ancient area was and where the centers of activities carried out by the people in the Ancient Kutai Kingdom at that time.